Strengthening learning during the COVID-19 pandemic with digital modules for class IV SD Negeri 1 Sindangkasih - Raden Fatia Hartini; Asep Mulyadi (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
During the COVID-19 pandemic, the Indonesian government took steps to impose restrictions on community activities that had an impact on the education sector. This has led to the re-implementation of learning activities from home which still need to be more effective. On the other hand, the difficulty in understanding learning material and the emergence of laziness in students to read the textbooks provided are problems that must be addressed immediately. One of the learning media that can be used to support learning activities at home is a learning module. Based on the results of previous research, this module is effectively used in learning in class IV SD Negeri 1 Sindangkasih. In the next stage, the module is used as material for a strengthening program for learning at home. The dedication method is strengthening the implementation of learning at home with the use of digital modules by parents of students. The results of the learning reinforcement program with digital modules are very effective for parents of students. Parents think using digital modules in learning at home is more structured and can clarify learning objectives at home. In addition to using digital modules, collaboration between teachers and parents is also a factor that needs attention to support the effectiveness of student learning activities at home.